An overview on light assisted techniques for waste-derived hydrogen fuel towards aviation industry. (15th February 2023) - Suresh, R.; Rajendran, Saravanan; Dutta, Kingshuk; Khoo, Kuan Shiong; Soto-Moscoso, Matias
Abstract: Aviation industry has a vital role in the economic growth and social development of the world. But, it shows negative impacts on the environment and thus this industry is looking for sustainable and clean fuel. Hydrogen energy is trusted as a promising fuel in the aviation industry, owing to the remarkable advantages. Different techniques, driven by thermal, light and electrical energies were developed for hydrogen production. Among others, light assisted hydrogen production techniques have been considered in this review. Here, we have briefed the significance of photofermentation, photochemical methods (biophotolysis, photocatalytic water splitting and photocatalytic reforming) and light assisted electrochemical methods (light assisted electrolytic cell, microbial fuel cell and photocatalytic fuel cell) in hydrogen production. This review is also particularly focused on the potential use of wastes as feedstock/substrate in the above mentioned methods. Importance of nanomaterials in light assisted hydrogen production techniques has been discussed. Advancements in the improvement strategies for the production of hydrogen with high rate and yield have also been discussed. Based on the literature review, current challenges have been proposed for advancing the research in this field. Highlights: Light assisted methods have been given much consideration for increasing the production of biohydrogen. This review has also considered the potential use of wastes as feedstock/substrate in the abovementioned methods. To improve hydrogen yield, different strategies and optimized experimental parameters have been reported.